KERAGAAN PERTUMBUHAN VEGETATIF MUCUNA BRACTEATA SEBAGAI AKOBAT PEMBERIAN PUPUK ZN - efi said ali (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
Agricultural development on peatlands faces many obstacles related to the nature of peat soils, in general the chemical properties of peat soils are dominated by organic acids which are the result of accumulation of plant residues. The organic acids produced during the decomposition process are substances that are toxic to plants, thus disrupting plant metabolic processes which will have a direct impact on their productivity. The high acidity of the soil in the peat area will make it difficult for Mucuna bractaeta to grow in the peat area. The results of the observation of the effect of Zn fertilizer have no significant effect on the parameters of tendril length, number of leaves, wet weight, and dry weight, although the index shows no treatment (Z0) visually better on the parameters of the length of the tendrils, and the number of leaves. Keywords: Agricultural, Mucuna Bracteta, Chemical.